The Impact of Government Subsidies and Quality Certification on Farmers’ Adoption of Green Pest Control Technologies - Yuying Yang; Yubin Wang (Agriculture)
Shandong and Henan provinces face significant pest and disease issues, creating a strong demand for green pest control technologies. This paper analyzes the impact of government subsidies and quality certification on farmers’ adoption of green pest control technologies, based on 419 survey responses collected through stratified sampling in Shandong and Henan provinces in 2024, using the Heckman two-stage model. The results show the following: (1) Government subsidies and quality certification significantly promote farmers’ adoption of green pest control technologies, with regression coefficients of 0.260 and 0.493, respectively. (2) An interaction effect exists between government subsidies and quality certification on farmers’ adoption of green pest control technologies, with a coefficient of 0.454. For a given government subsidy, higher quality certification levels increase the likelihood of farmers adopting green pest control technologies. (3) From the perspective of human capital quantity, there is obvious heterogeneity in the impact of government subsidies and quality certification on farmers’ adoption of green pest control technologies. (4) From the perspective of generational differences, quality certification has obvious heterogeneity on farmers’ adoption of green pest control technologies, while there is no obvious generational difference in government subsidies. Therefore, it is necessary to establish a stable and multi-channel government transfer payment system, improve the construction of the agricultural product quality traceability system, take a two-pronged approach, and complement each other’s strengths to build a targeted incentive mechanism based on different groups of farmers.